SUSTAINABLE ECONOMIC DEVELOPMENT OF ENTERPRISES (World Economics and Finance Bulletin, 2024)
At the present time, an effective methodological toolkit has not been developed to manage economic processes in modern conditions in order to ensure the sustainable economic development of enterprises. On the basis of mathematical modeling, it has been proposed that such a tool could be created to provide a quantitative assessment of the main parameters in the creation of innovative products and activities of enterprises. Additionally, on the basis of this tool, decision makers could regulate these processes by introducing additional resources and buying risks. For this purpose, it is necessary to modernize the means of production, which requires a reassessment of the technical level of enterprises. It is possible to achieve these parameters through a certain technical policy of production modernization. In this aspect, the technical policy of enterprises should consider the fact that, depending on the complexity of innovative products put for development and production, the time lag between the start of production of such products and the moment when they enter the market with competitive advantage changes.